Relação do consumo de alimentos promotores e protetores de doenças cardiovasculares com o estado nutricional e aspectos sociodemográficos de discentes de uma instituição de ensino superior - SOUSA, Herison Diego Abreu de (2023)
In this study we aim to verify the association of the intake of promoter food and protectors of cardiovascular diseases with the nutritional status and sociodemographic aspects of students of a higher education institution. It was a crosssectional study with nonprobabilistic sampling for the convenience of active students and regularly enrolled in one of the undergraduate courses of the Institute of Health Sciences (ICS) of the Federal University of Pará (UFPA). The data were collected through an online questionnaire. SPSS version 20 (IBM, USA) was used to analyze the data. We did a descriptive statistic for all study variables. Descriptive statistics were performed for all study variables. MannWhitney and KruskalWallis tests were used to verify the statistical difference between the variables of the study and was adopted the pvalue of less than 5%. A total of 332 students were evaluated, 107 males and 225 males, mean age 23±4 years and body mass index of 23.5±4.5 kg/m². Of the participants, 51.5% had income of up to 03 minimum wages. More than half of the participants are eutrophic (60.2%) and approximately 31% of them are overweight. There was a statistically significant difference between the promoter foods and the body mass index (p = 0.012), and the higher the BMI, the higher was the mean intake score of foods that promoted cardiovascular diseases (9.11 ± 4.6). A higher score of cardiovascular diseasepromoting foods was observed among overweight participants. In addition, the highest scores of protective food for CVD were found among those in stable union.